1958
DOI: 10.1017/s0031182000021028
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic study of Trypanosoma cruzi in thin sections of infected tissue cultures and of blood-agar forms

Abstract: Thin sections of Trypanosoma cruzi in tissue cultures and from blood agar medium have been examined with the electron microscope.In the leishmania and crithidia forms of the parasite a neat separation of kinetonucleus and blepharoplast has been obtained and these structures are described. The blepharoplast is the row of basal corpuscles which give origin to the axial fibres of the flagellum.Division of the parasite seems to begin in the basal corpuscles; it is followed by binary division of the kinetonucleus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

1960
1960
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 7 publications
2
35
0
1
Order By: Relevance
“…It is bounded by a double membrane and within it is a fibrillar material presumed to contain DNA (3). A more or less similar appearance has been observed in the kinetonuclei of T. equiperdum by Anderson et al (10) and of T. cruzi by Meyer et al (11). In favorable sections, it is seen that the kinetonucleus extends into structures with the typical features of mitochondria, including inner membranes or "cristae" (Figs.…”
Section: Observations and Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is bounded by a double membrane and within it is a fibrillar material presumed to contain DNA (3). A more or less similar appearance has been observed in the kinetonuclei of T. equiperdum by Anderson et al (10) and of T. cruzi by Meyer et al (11). In favorable sections, it is seen that the kinetonucleus extends into structures with the typical features of mitochondria, including inner membranes or "cristae" (Figs.…”
Section: Observations and Discussionsupporting
confidence: 76%
“…limited knowledge of the ontogenesis of mitochondria. It is probable that future investigations will show the mitochondrial nature of unidentified bodies associated with the kinetonuclei of another trypanosome (11) and of a bodonid (15). The only mitochondrial-nucleus association approaching this in other cells is that described in the ameba, Chaos chaos, by Brandt and Pappas (16) who discuss it in terms of mitochondrial formation by the nucleus.…”
Section: Figunementioning
confidence: 99%
“…Early studies using electron microscopy (Meyer et al 1958) identified a dark, electron dense and slightly bent inclusion, corresponding to a structure known at that time as the kinetonucleus, which had been previously identified by light microscopy of stained cells. This structure is now known as the kinetoplast.…”
Section: The Kinetoplast-mitochondrion Complexmentioning
confidence: 88%
“…The remarkable molecular configuration of the kDNA network (279,326,360) continues directly into a typical mitochondrion canal system, as seen for any tissue cell (309). The kDNA is located within the mitochondrial matrix, and the position of the kinetoplast relative to the nucleus changes during the cell life cycle.…”
Section: Kinetoplast Dnamentioning
confidence: 93%